2022
DOI: 10.1590/0034-7167-2021-0756
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Central Nervous System drug use among nursing students

Abstract: Objectives: to verify sociodemographic, academic and health risk factors for Central Nervous System drug use among nursing students. Methods: a cross-sectional study with 199 public undergraduate students from Ceará, using Characterization Instrument, Antonovsky’s Sense of Coherence Questionnaire, Beck Depression Inventory and Beck Anxiety Inventory. Fischer’s exact test and Pearson’s chi-square test were performed, verifying an association between variables. Prevalence ratio was used. Results: a total of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…An integrative review on factors associated with mental health in undergraduate students pointed out that a high SOC score can be a protective factor, capable of influencing coping strategies and reducing psychological distress ( 12 ) . A Brazilian study showed that students with lower SOC had almost 3 times higher prevalence of using drugs that act on the Central Nervous System, which in turn shows the relationship between SOC and mental disorders ( 13 ) . Such findings highlight the need for further studies exploring interventions aimed at increasing SOC in promoting mental health.…”
Section: Introductionmentioning
confidence: 99%
“…An integrative review on factors associated with mental health in undergraduate students pointed out that a high SOC score can be a protective factor, capable of influencing coping strategies and reducing psychological distress ( 12 ) . A Brazilian study showed that students with lower SOC had almost 3 times higher prevalence of using drugs that act on the Central Nervous System, which in turn shows the relationship between SOC and mental disorders ( 13 ) . Such findings highlight the need for further studies exploring interventions aimed at increasing SOC in promoting mental health.…”
Section: Introductionmentioning
confidence: 99%